Casting the Tax Net Wider : Experimental Evidence from Costa Rica - Brockmeyer, Anne; Hernandez, Marco; Kettle, Stewart; Smith, Spencer (World Bank, Washington, DC, 2016)
The majority of firms in developing countries are informal, and encouraging them to register with the tax authority has proven challenging and costly. This paper argues that incomplete tax filing among registered firms constitutes an important intermediate form of informality, which can be tackled with much higher cost-effectiveness. Using a nationwide randomized experiment in Costa Rica, The paper shows that credible enforcement emails tripled the income tax filing rate and doubled the payment rate among previously non-filing firms. The treatment effect was even higher when the email listed examples of third-party reports of a firm's transactions, with the return on an email reaching US$ 19. It also shows that the intervention had no negative spillovers on other tax compliance dimensions, the treatment effects persisted in the medium term, and treated firms became more likely to file information reports about their suppliers or clients, thereby increasing the tax authorities' information set for future tax enforcement.